Solar distillation using three different phase change materials stored in a copper cylinder. (November 2019) - Sonker, Varun Kumar; Chakraborty, Jyoti Prasad; Sarkar, Arnab; Singh, Rishikesh Kumar
Abstract: The present study focuses on the design and fabrication of passive solar still system with phase change materials (PCM). In order to improve the distillate, PCMs (paraffin wax, stearic acid, and lauric acid) have been stored in a copper cylinder. The effects of basin water depth on total distillate have been studied for all three cases. The maximum distillate has been obtained at 1 cm depth for all cases with three PCMs used in this study. Total distillate decreased linearly with water depth for all three PCMs. There has been a 9.2% drop in the maximum water basin temperature in paraffin wax as compared to stearic acid (17.6%) and lauric acid (21.5%) with an increase in water depth from 1 to 5 cm. Heat transfer and energy balance equations involved in the present solar still system have been stated. Variation of some heat transfer coefficients with time has also been studied for three different PCMs. The total distillate has been found to be increased by 1202, 1015, and 930 ml/m 2 -day for paraffin wax, stearic acid, and lauric acid, respectively stored in a copper cylinder. The performance of lauric acid for total distillate has been comparable with the other two PCMs.